India Social Development Report 2023 : Women's contribuion in the economy - Council for social development (New York : Oxford University Press, 2024)
This report highlights that gender inequalities and women's subordination in India are caused by two formidable macro-structures: patriarchy and the exclusion of unpaid work from the macro-economy. Both these structures reinforce each other and negatively impact women's empowerment. Patriarchy imposes subordination on women and forces a disproportionately higher share of unpaid domestic services and unpaid care onto them. This is unfair and unjust - a violation of basic human rights. Other structures like race, religion, and caste cut across these main structures. The selected papers in this report show how patriarchy causes gender inequalities in all critical dimensions of women's life on the one hand, and how unpaid domestic services and unpaid care sustains the macro-economy and its growth on the other. The contributors discuss pathways to integrate unpaid work with the macro-economy such that the strength of patriarchy declines and at the same time gender equality is promoted. To put it differently, unless the structures are addressed by integrating unpaid work, inequalities cannot be addressed effectively. The report emphasizes that this is the only way to move to real macroeconomics. The papers have explored pathways to break these structures gradually to achieve gender equality and empower women. Though the path is challenging, it is feasible to reach the goal of pervasive gender equality.
Keywords: Economic development -- Social aspects -- India; Women -- Social conditions -- 21st century -- India; Business & Economics / Labor / General